CANDIDATES FOR A GLOBAL STRATOTYPE OF THE INDUAN-OLENEKIAN BOUNDARY (LOWER TRIASSIC) IN SOUTHERN PRIMOR'E - Zakharov Yu.D.; Popov A.M.; Burii G.I.; Golozubov V.V.; Shigeta Y.; Sokarev A.N. (My University, 2002)
The Lower Triassic section in the Abrek Bay region, southern Primor'e, is described in detail along with its lithologic, paleontological, and magnetostratigraphic characteristics. This and another section in the Tri Kamnya Cape region, southern Primor'e, are proposed as candidates for the Global Stratotype Section and Point of the Induan-Olenekian boundary. The base of the Olenekian Stage is defined at the appearance level of ammonoid genera Hedenstroemia and Meekoceras.
Keywords: Triassic; Olenekian; Induan; Mesozoic::Triassic; Мезозой::Триасовая; Мезозой::Триасовая::Нижний::Оленёкский; Мезозой::Триасовая::Нижний::Индский; Mesozoic::Triassic::Lower::Olenekian; Mesozoic::Triassic::Lower::Induan